Recreational motor vehicle use and facial trauma. (12th October 2015) - Shaigany, Kevin; Abrol, Anish; Svider, Peter F.; Eloy, Jean Anderson; Carron, Michael A.; Lin, Ho‐Sheng; Folbe, Adam J.
Abstract : Objectives/Hypothesis: The use of recreational motorized vehicles (RMVs), including all‐terrain vehicles (ATVs), snowmobiles, and go‐carts, has increased in recent decades. Because RMVs are lightly regulated, there are numerous safety concerns. This analysis examines a nationally representative resource to estimate the incidence of craniofacial trauma secondary to RMV accidents, evaluating injury and demographic patterns. Methods: The Consumer Product Safety Commission's National Electronic Injury Surveillance System was examined for facial trauma resulting in emergency department (ED) visits stemming from the use of ATVs, motorbikes/scooters, snowmobiles, and utility vehicles. Characteristics including demographics, anatomic sites, mechanism, and location of injury were evaluated, as well as details regarding helmet and alcohol use. Results: There were 1, 464 entries extrapolating to an estimated 61, 312 ED visits over a 5‐year period for facial trauma from RMV use. From 2009 to 2013, there was a 28% reduction in ED visits. The majority of patients were male, and the median age was 17 years. Lacerations (45.1%), contusions/abrasions (26.7%), and fractures (24%) were the most frequent injuries. Among fractures, the most common types were nasal (29%), followed by mandible (20%) and orbital (8%) fractures. All‐terrain vehicles (62%) were the most common vehicles. Alcohol consumption resulted in a higher rate of facial fractures (48.5% vs. 22.8%). Conclusion: As there is a significant potential for injury, familiarity with injury patterns associated with RMVs is useful in the management of facial trauma. Recreational motorized vehicles facial trauma results in tens of thousands of ED visits annually. This data reinforces the importance of pursuing further efforts to raise public awareness and improve safety measures. Level of Evidence: 4. Laryngoscope, 126:67–72, 2016